Análisis y evaluación de la identidad e imagen corporativa de las cooperativas de ahorro y crédito de la ciudad de Latacunga - Chiliquinga Guzmán, Amanda Gabriela (2016)
This research refered to the development of a plan to improve corporate image and identity at cooperatives of saving and credit in Latacunga in order to provide solutions efficiently to the existing problems in the workplace.The work done at the initial stage was developed in order to determine the level of the staff`s knowledge about what is identity and corporate image. It was focused on topics such as marketing, public relationship, labor relationship, identity and corporate image and finally at cooperatives of saving and credit.In the middle phase of the investigation, surveys were applied to members and financial entities to obtain real and valuable information….